(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
Human remains identification, that is, the ability to allocate a name to an unidentified person, is an important part of a wider and complex multidisciplinary process and represents, in forensic and humanitarian contexts, a need for the society as a whole but also a fundamental right of all individuals and their families to avoid the flail of ambiguous loss for relatives seeking for their loved ones. Forensic Anthropologist plays a central role in positive identification of human remains both for the construction of a general identity, i.e., the biological profile, where an identikit is built from the remains and for the process of personal identification, i.e., that of identifying the remains as those of a known person and of attributing the correct name to the person.